Princes, peasants, and other Polish selves - Gladsky, Thomas S. (Univ. of Massachusetts Pr., 1992)
This book is a case study of the way in which ethnic identities are created and shaped by literature, focusing on the American image of the Pole from the 1830s to the present. Using a vast range of writings, some well known and others long neglected, Thomas S. Gladsky shows how the nineteenth-century view of the Pole as kindred spirit or
Keywords: Amerikaans; Américains d'origine polonaise - Vie intellectuelle; Américains d'origine polonaise dans la littérature; Caractéristiques nationales dans la littérature; Ethnicité dans la littérature; Etnisch bewustzijn; Letterkunde; Littérature américaine - Auteurs américains d'origine polonaise - Histoire et critique; Littérature américaine - Influence polonaise; Pologne dans la littérature; Polonais dans la littérature; Pools; Literatur; Polnisch; American literature; Ethnicity in literature; National characteristics; Polish; in literature; Polish Americans in literature; Polish Americans; Polish people in literature; Nationalcharakter